Spillover from the Haven: Cross-border Externalities of Patent Box Regimes within Multinational Firms - Thomas Schwab; Maximilian Todtenhaupt (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We analyze cross-border externalities of patent box regimes. Tax cuts in one location of a MNE reduce the user cost of capital for the whole group if they have no nexus requirement. This spillover effect of foreign tax cuts raises domestic R&D activity. The implementation of a patent box in an affiliate country of a MNE, increases domestic R&D by about 1% per implied tax rate differential. Furthermore, patent boxes generate negative spillovers on average patent quality.
Keywords: H23; 330